Flipped Classroom Using Screencast-O-Matic Apps in Teaching Reading Skill in Indonesian Language - Cahyo Hasanudin; Ayu Fitrianingsih (International Journal of Pedagogy and Teacher Education, 2018)
This article aims to describe the implementation of the flipped classroom method using Screencast-O-Matic apps in the teaching of Indonesian language reading skills and the impact this method has on the learning process. This qualitative research was conducted at one of the private institutes in Bojonegoro, Indonesia, and the researcher acted as the observer. The data were obtained through interviews, classroom observations, and document analysis, and were analysed using Creswell’s thematic analysis, which involves six stages of analysing and intrepreting. Then, the data were validated using triangulations of theory and source. The results of this research show that Screencast-O-Matic apps contribute to the successful implementation of the flipped classroom method. The combination of the teaching method and the media creates innovation in teaching reading skills in the Indonesian language. In the teaching and learning process, the teacher acts as the facilitator, resulting in some good impacts for the students: 1) the students are motivated by the video study materials, 2) the students are able to enjoy their leisure time, 3) the students are pleased with the teaching and learning process and are able to answer questions quickly, 4) the students appreciate each other’s opinions, and 5) the students have more comprehensive knowledge of the Indonesian language reading skills materials.